(untitled) (Journal of Naval Architecture and Marine Engineering, 2023)
A breakwater is a structure used to dissipate the wave energy in order to protect the shore and maintain tranquility inside the harbor basin. The quarter-circle breakwater (QBW) constitutes of a quarter circular front wall facing incident waves, a vertical rear wall, and a horizontal base slab placed on a rubble mound foundation. In this study, a comprehensive experimental investigation is carried out in order to examine the wave overtopping characteristics of a non-perforated and seaside perforated emerged quarter-circle breakwater subjected to regular waves. A model scale of 1:30 is selected based on the limitations of testing facilities. For the current investigation, QBW models of the radius 0.50 m are utilized. The model is tested for six different perforations ranging between 0% and 20%, with a constant perforation radius of 0.016 m. The paper highlights the influence of wave steepness (Hi/gT2), relative crest freeboard (Rc/Hi), relative water depth (d/gT2) on the wave overtopping performance of the seaside perforated and non-perforated QBW models. An increase in wave steepness is found to increase the dimensionless mean wave overtopping discharge. Also, an exponential decrease in dimensionless mean wave overtopping discharge is observed with an increasing relative freeboard. The relative freeboard is found to be one of the predominant parameters influencing the wave overtopping discharge rate.